The Effect of Remap Cooperative Script (Remap-CS) Learning with Wordwall Assistance on Students’ Critical Thinking Ability - Saputri, Wahyu Dina; Dewi, Novi Ratna (Universitas Negeri Semarang, 2022)
The learning model that can improve students’ critical thinking skills is the Remap Cooperative Script model with the help of Wordwall. This study aims to determine the effect of Remap Cooperative Script assisted by Wordwall on critical thinking skills and to determine student responses from the application of the model. The research method used is a quasi-experimental design. The sample in this study was taken by cluster random sampling technique. The effect of the Wordwall-assisted Remap Cooperative Script model was analyzed using the related t-test. Improvements in critical thinking skills were measured using N-Gain, and measured the results of student response analysis. The influence of Remap Cooperative Script assisted by Wordwall on students’ critical thinking skills as measured by the final related t-test test of 4.12 indicates that there is an influence from the application of the model on students’ critical thinking skills. The increase in students’ critical thinking skills as measured using N-gain in the experimental class was 0.53 while the control class was 0.38. These results indicate that there is a difference in the increase between the experimental class and the control class due to the treatment given. The results of the study were also supported by a very good student response of 82.11%. Based on this, it is concluded that learning using the Remap Cooperative Script model with the help of Wordwall has an effect on increasing students’ critical thinking skills